Cardiology consultation for non-cardiac surgery: Medical and legal explorations for clinicians. (15th September 2018) - Patel, Nachiket J.; Paterick, Zachary R.; Schmidt, Matthew; Jamil Tajik, A.; Paterick, Timothy E.
Abstract: Cardiologists performing preoperative cardiac evaluations for non-cardiac surgery have a unique opportunity to assess and optimize the patient's baseline and general health; determine the patient's inherent surgical risk based upon a comprehensive history, physical examination and pertinent laboratory data; ensure the patient has made an informed choice regarding surgery, and identify post-operative risks that must be considered to reduce the potential for major adverse cardiovascular events. There is always a small but inherent risk in surgical procedures. When an adverse outcome occurs there is potential for an allegation of negligence resulting in a detailed autopsy of the medical record. The best defense to an allegation of negligence is comprehensive documentation and a detailed rational for the cardiologist's management decisions.